Serum interleukin 17 concentrations in dogs with immune‐mediated hemolytic anemia. (21st November 2020) - Cuq, Benoît; Blois, Shauna L.; Bédard, Christian; Wood, R. Darren; Abrams‐Ogg, Anthony C.; Beauchamp, Guy; Wood, Geoffrey A.
Abstract: Background: Increased serum interleukin 17 (IL‐17) concentration has been associated with the immunopathogenesis of autoimmune hemolytic anemia in humans. No data are available about IL‐17 in immune‐mediated hemolytic anemia (IMHA) of dogs. Objectives: Monitor changes in serum IL‐17 concentration during the acute stages of IMHA in dogs, compared with results in healthy dogs, and its relationship with outcome. Animals: Thirty‐one client‐owned dogs with primary IMHA and 27 healthy dogs. Methods: Quantification of serum IL‐17 concentration using a commercially available ELISA kit at the time of admission (D0), after 48 hours (D2) and after 96 hours (D4) as compared to concentration in healthy dogs. The IMHA dogs were classified as survivors if discharged from hospital, or nonsurvivors for any cause of in‐hospital mortality. Results: Mean serum IL‐17 concentration was higher in dogs with IMHA on admission compared with healthy dogs (D0), but this difference was not significant (mean, 19.52 pg/mL vs 10.52 pg/mL, respectively, P = .17). Throughout hospitalization, serum IL‐17 concentration significantly decreased in survivors. Serum IL‐17 concentration at D0 was not different between survivors and nonsurvivors, but surviving dogs had significantly lower serum IL‐17 concentration at D2 and D4 ( P = .04 and P = .004, respectively) compared with nonsurviving dogs. No correlation was found between serum IL‐17 concentration and serum total bilirubin or lactate concentrations or CBC parameters. Conclusion and Clinical Importance: Serum IL‐17 concentration remained significantly higher in nonsurviving IMHA dogs whereas it significantly decreased during hospitalization in survivors, making serum IL‐17 concentration a potential biomarker for severity and response to treatment in IMHA.